Analisis Sejarah Candi Tinggi Jambi Sebagai Pusat Kebudayaan dan Agama - Maulidya, Rosdiana; Alfarros, Muhammad Luthfi; Irfandi, Ahmad; Gunawan, Aldi; Syamsiah, Syamsiah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Candi Tinggi Jambi is one of the most significant archaeological sites in the province of Jambi, Indonesia. It serves as a vital marker of the region's cultural and religious history, especially during the Srivijaya and Malayu kingdoms. This study aims to explore the historical background, significance, and the role of Candi Tinggi as a center for both culture and religion. By examining inscriptions, artifacts, and architectural elements, the research provides insights into the temple’s role in the social and religious life of its time. The study also investigates how Candi Tinggi influenced the spread of Hindu-Buddhist beliefs in Southeast Asia. It highlights the importance of such historical sites in understanding the religious, cultural, and political dynamics of ancient Southeast Asian kingdoms. This paper employs historical analysis and archaeological research methods to uncover the significance of Candi Tinggi in shaping the region’s identity and cultural heritage.